Overcrowding in Psychiatric Wards is Associated With Increased Risk of Adverse Incidents. Issue 3 (March 2016) - Teitelbaum, Alexander; Lahad, Amnon; Calfon, Nitza; Gun-Usishkin, Monica; Lubin, Gad; Tsur, Anat
Abstract : Objective: To study the association between bed occupancy in psychiatric wards and rate of adverse incidents (AIs) including aggressive behavior and falls. Methods: This is a retrospective study analyzing bed occupancy and AIs' data in 4 closed wards in a state psychiatric hospital in Israel over a 20-month period. Ward-level daily records were extracted from the hospital's electronic admission-discharge and AI registries, creating a log of 609 days for each of the 4 wards. Relationships between gross and net bed occupancy and AIs rate were calculated, in general and for each ward and type of incidents. Results: Average gross occupancy was 106±14.8% and net occupancy was 96.4±15.6%. Gross occupancy >100% was recorded in 51% of days. Net occupancy was higher on days with at least 1 incident than on no-incident days (98.6±14.8% vs. 95.7±15.7%, P <0.0001). AIs occurred in 18.6% of days in the lowest occupancy quadrant (up to 85% occupancy), compared with 26.7% of days in the highest occupancy quadrant (106% and above). Moreover, aggressive behavior-type incidents were significantly lower in the lowest occupancy quadrant days compared with the highest occupancy quadrant (8.3% vs. 14.1%, P <0.01). Evidence of a dose-response effect of bed occupancy on AIs rate was found. Conclusions: Overoccupancy is prevalent in psychiatric wards and is associated with an increased rate of aggressive AIs and falls. Policy makers should be convinced about the necessity to reduce overcrowding in psychiatric wards and to improve safety of inpatient facilities.